THE IMPLEMENTATION OF CASHLESS ZONE AS A STRATEGY TO PREVENT CORRUPTION IN INDONESIA - Fatria Khairo (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
There are many ways to solve the problem of corruption in Indonesia. Therefore, this paper aims to analyze the corruption prevention strategy by implementing Cashless Zone culture as one of the alternatives to prevent corruption in Indonesia, in addition to enforcing control functions over budget planning and its execution, establishing honesty, and building leadership role-model.